Emotional reactivity, trauma-related distress, and suicidal ideation among adolescent inpatient survivors of sexual abuse. (March 2019) - DeCou, Christopher R.; Lynch, Shannon M.
Abstract: Adolescent psychiatric inpatients suffer high rates of childhood sexual abuse, trauma-related distress, and suicidality. This study evaluated the hypothesis that three domains of resiliency (i.e., Sense of Mastery, Sense of Relatedness, and Emotional Reactivity) would mediate the effect of trauma-related distress upon suicidal ideation, while accounting for symptoms of depression, and that the indirect effect of trauma-related distress upon suicidal ideation would be greater among survivors of childhood sexual abuse. Chart review patients included 550 adolescents admitted to a public psychiatric hospital in a Northwestern US State from 2010 to 2015. Adolescents completed self-report measures of trauma-related distress, depression, resiliency, and suicidal ideation. Half of the adolescents in this study reported past history of childhood sexual abuse, and more than half disclosed history of attempted suicide. There was a group noninvariant indirect effect of trauma-related distress upon suicidal ideation via emotional reactivity among survivors of childhood sexual abuse ( β  = 0.10, 95% ACI: 0.04 to .17), as well as a group invariant direct effect of depression symptoms ( β  = 0.88, p  < .001). The other two domains of resiliency, sense of mastery and sense of relatedness did not mediate the association between trauma-related distress and suicidal ideation. These findings demonstrate the importance of emotional reactivity with regard to suicidal ideation, as well as the association between depression symptoms and suicidal ideation in this clinical population, and suggest the potential utility of skills-based interventions, and the need for trauma-informed policy and procedures in adolescent psychiatric inpatient settings.